PREVALENCE OF DRUG USE AMONG PREGNANT WOMAN (CIPEEX, 2022)
THE USE OF PSYCHOACTIVE SUBSTANCES, LEGAL OR ILLEGAL, BY PREGNANT WOMEN IS AN INCREASINGLY RECURRENT PRACTICE IN TODAY'S SOCIETY. IN THIS PERSPECTIVE, THE PRESENT ANALYSIS IS A MINI-INTEGRATIVE LITERATURE REVIEW THAT AIMED TO IDENTIFY, AMONG THE DRUGS CONSUMED BY PREGNANT WOMEN, WHICH ARE THE MOST RECURRENT, IN ADDITION TO ESTIMATING THE PREVALENCE AND SOCIAL AND ECONOMIC DETERMINANTS OF DRUG USE IN PREGNANT WOMEN. KNOWING THIS OBJECTIVE, THE SOCIAL DETERMINANTS THAT INFLUENCE THESE ADDICTIONS WERE EVALUATED, SUCH AS: AGE, LEVEL OF EDUCATION AND LEVEL OF PRENATAL CARE. THEREFORE, FIVE ARTICLES FROM THE PUBMED AND SCIENTIFIC ELECTRONIC LIBRARY ONLINE (SCIELO) DATABASES WERE USED, FOUND THROUGH THE DESCRIPTORS €ŒILLICIT DRUGS IN PREGNANT WOMEN€. BASED ON THIS, IT WAS FOUND THAT ALCOHOLISM AND SMOKING ARE THE DRUGS WITH THE HIGHEST PREVALENCE AND RECURRENCE AMONG PREGNANT WOMEN AND THAT THE SOCIAL DETERMINANTS THAT INCREASE THE PROBABILITY OF THIS SITUATION ARE AGE, TIME OF STUDY, FAMILY INFLUENCE, LACK OF RESOURCES AND PROFESSIONAL FOLLOW-UP. THEREFORE, IT IS CONCLUDED THAT COUNSELING AND MEDICAL FOLLOW-UP WITH PREGNANT WOMEN REGARDING THE USE OF NARCOTICS DURING PREGNANCY IS NECESSARY, SO THAT THIS SITUATION DOES NOT BECOME EVEN MORE PREVALENT.
Keywords: illicit drugs; pregnant women; drugs